Exploring The Impact of Self-Regulated Learning on Reducing Students' Mathematics Anxiety - harahap, Lidra Ety Syahfitri; Sri Andayani; Ekwan, Deflimai (Hipotenusa: Journal of Mathematical Society, 2024)
The study of mathematics often presents challenges due to anxiety, which can adversely affect students' understanding and performance. Research on self-regulated learning has received increasing attention as a strategy to address this issue. This article presents a comprehensive literature review to explore the relationship between self-regulated learning and anxiety in mathematics. Using the PRISMA procedure, 28 studies were selected from 2018 to 2024 to explore the relationship between self-regulated learning and math anxiety grouped by level of research, methodology, sample, and instruments used. The review showed that stronger levels of self-regulated learning were associated with lower levels of math anxiety, while lower levels of self-regulated learning were associated with higher math anxiety. These findings provide valuable insights for educators and researchers in developing strategies to increase self-regulated learning and reduce students' math-related anxiety. Understanding these relationships makes it possible to design more targeted interventions to improve teaching practices as well as student learning outcomes in mathematics.